2017
DOI: 10.1038/s41398-017-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

“DNA Methylation signatures in panic disorder”

Abstract: Panic disorder (PD) affects about four million Europeans, with women affected twice as likely as men, causing substantial suffering and high economic costs. The etiopathogenesis of PD remains largely unknown, but both genetic and environmental factors contribute to risk. An epigenome-wide association study (EWAS) was conducted to compare medication-free PD patients (n = 89) with healthy controls (n = 76) stratified by gender. Replication was sought in an independent sample (131 cases, 169 controls) and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 86 publications
0
66
1
1
Order By: Relevance
“…Furthermore, there were 9341 (2.99%) CpG probes with even lower maximum value than that of cg05293407 TRIM27 indicating its narrow range was reasonable. Meanwhile, plenty of studies have revealed that aberrant DNA methylations of these hypo-methylated CpG probes were also involved in diseases (e.g., female panic disorder risk associated cg07308824 HECA and paediatric medulloblastoma prognosis associated cg02257300 ERCC2 ) [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there were 9341 (2.99%) CpG probes with even lower maximum value than that of cg05293407 TRIM27 indicating its narrow range was reasonable. Meanwhile, plenty of studies have revealed that aberrant DNA methylations of these hypo-methylated CpG probes were also involved in diseases (e.g., female panic disorder risk associated cg07308824 HECA and paediatric medulloblastoma prognosis associated cg02257300 ERCC2 ) [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…They depicted forty CpG sites significant associated with PD at 5% FDR correction, but with small different rates of the DNA methylation. A study that compared medication-free PD patients with healthy controls 25 suggested a possible sex-specific methylation process (hypermethylation in female patients) in the HECA gene, but no global changes in DNA methylation. Schartner et al .…”
Section: Discussionmentioning
confidence: 99%
“…Given the current state of knowledge on the genetics of anxiety disorders, unbiased hypothesis-free methodology might be more fruitful for investigating the DNA methylation fingerprints related to the course of these disorders 19 21 . To our knowledge there is a paucity of studies involving genome-wide DNA methylation and anxiety in humans 22 25 and in animals 26 studies.…”
Section: Introductionmentioning
confidence: 99%
“…EWAS can be used to analyze genome-wide associations between epigenetic changes and disorders, and several EWAS for multifactorial disorders, including mental disorders, have been reported (Abdulrahim et al 2019;Starnawska et al 2019;Gonzalez-Jaramillo et al 2019). Iurato et al (2017) conducted an EWAS in a sample of 89 patients with PD and 76 controls. In the female sample, one locus with genome-wide association was detected in the enhancer region of the hdc homolog, cell cycle regulator (HECA) gene (cg07308824: p = 1.094 × 10 −7 ; p-adj = 0.046).…”
Section: Epigenome-wide Association Studies (Ewas) Of Pdmentioning
confidence: 99%